Pulse dose glucocorticosteroid therapy in COVID-19 pneumonia patients in an intensive care unit - İlkay Ceylan; Gürcan Güler; Korgün Ökmen; Halil Erkan Sayan; Ebru Karakoç (National Scientific Medical Center, 2022)
Introduction: Coronavirus pneumonia occurs with severe lung tissue damage and rapid activation of cytokines and chemokines, called "cytokine storm," and simultaneously with a high risk of thrombosis and thromboembolism. There is no specific therapy for new coronavirus infection (COVID-19) also for cytokine storm. Therefore it is necessary to search for effective anti-inflammatory treatment. The aim of this study is to investigate the efficacy of pulse-dose glucocorticosteroid use in the treatment of COVID-19 patients hospitalized in the intensive care unit. Material and methods: The efficacy of pulse dose glucocorticosteroid therapy with 250-1000 mg for three days methylprednisolone 1 mg/kg for 5-7 days more in 144 patients in an intensive care unit with severe coronavirus pneumonia was studied in a retrospective analysis of 55 patients in the standard dose glucocorticosteroid (1 mg/kg/day methylprednisolone) group. The study's primary endpoint was mortality in ICU, and the secondary endpoint was the effects on inflammatory markers. The treatment groups' disease severities were initially the same. Results: Pulse dose glucocorticosteroid therapy did not reduce overall intensive care mortality but also increased it. C-reactive protein and fibrinogen levels decreased statistically significantly from the 1st day of admission, but D-dimer did not change statistically significantly. Neutrophilia was seen after steroid use, but it was significantly higher in the pulse dose group. Recovery in the pulse dose group was slower (median ICU stay was 12 days in the pulse dose group versus 10 days in the standard dose group, p=0.002) Conclusion: Pulse dose glucocorticosteroid therapy has a rapid anti-inflammatory effect but did not reduce intensive care mortality, also increased intensive care length of stay in our cohort.